Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4028/www.scientific.net/kem.824.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Environmentally Friendly Fabrication of Silver Nanoparticles Using Rambutan Peel Extract

Abstract: Silver nanoparticles (AgNPs) have been intensively researched because of their wide range of applications in the areas of catalysis, optics, antimicrobials and biomaterials production. The pH of the reaction mixture is one of the crucial parameters for improving the properties of AgNP, including size, morphology and agglomeration. In this study, AgNPs were synthesized by a biological method using rambutan peel extract. The effect of pH on the resultant biogenic AgNPs was observed by varying the pH values to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Antioxidant activities including ferric-reducing antioxidant power (FRAP) and DPPH radical scavenging activity were evaluated. These colorimetric methods were carried out as previously described [27].…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…Antioxidant activities including ferric-reducing antioxidant power (FRAP) and DPPH radical scavenging activity were evaluated. These colorimetric methods were carried out as previously described [27].…”
Section: Phytochemical Contentsmentioning
confidence: 99%
“…The green synthesized ZnO NPs maintained their antibacterial activity (MIC and MBC values) throughout the incubation period, irrespective of the cationic salts (Table 4). A modification of the physicochemical conditions such as pH and ionic strength of the solution can affect the intrinsic properties of NPs, such as their size, stability, zeta potential, morphology and shape [16]. Therefore, the stability of the green synthesized ZnO NPs at varying pH values (4,6,8) was estimated by determining their antimicrobial activity against the MDR-EAEC strains.…”
Section: In Vitro Stability Assays Of Zno Npsmentioning
confidence: 99%
“…3.5.1 Effect of pH. The pH is known to be a significant parameter in controlling the size, morphology, and stability of AgNPs [ 330 ]. Singh et al [ 331 ] synthesized spherical AgNPs using Hibiscus leaf extract ranging 12–17 nm in diameter.…”
Section: Reviewmentioning
confidence: 99%
“…It was also reported that a change in pH affects the reducing capability of the extract, which is also confirmed by other studies [ 333 334 ]. The pH is also reported to control the zeta potential [ 330 , 332 ] and results in particle stability adjustments [ 330 ]. The higher the value of the zeta potential, the stronger the long-term stability of the AgNPs, thereby preventing their agglomeration [ 330 , 335 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation